’Terminologi’ se ’leksikografi’, ’leksikografi’ se ’ordbog’ - Leroyer, Patrick (LexicoNordica, 2005)
Anmeldt værk: Colette Cortès (red.): Des fondements théoriques de la terminologie. Cahier du C.I.E.L. 2004. Paris: Université de Paris 7 Denis Diderot, UFR E.I.L.A. [166 sider, pris € 12,-] In light of the polemic debate between terminologists and lexicographers over the years, the relationship between terminography and specialized lexicography remains unclear. Bergenholtz et al. 1994 were criticized by Puuronen 1995 for not applying terminological methods and confusing terms with concepts. Ten years have passed since then, and this article shows that some major, new contributions reviewed here indicate that the debate – and the criticism – are now obsolete as there seems to be a consensus that the complex needs of dictionary users in professional settings and in corporations should be taken into account. Here lies the best guarantee for the joint planning of problem solving dictionary solutions. Surprisingly enough, this is more or less exactly what E. Wüster, the founding father of terminology, also had in mind.